2009
DOI: 10.1111/j.1540-5885.2009.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Voices from the Field: How Exceptional Electronic Industrial Innovators Innovate

Abstract: This exploratory research uses in‐depth qualitative interviews to investigate how 11 exceptional innovators in the electronics industry initiated, created, and commercialized radical innovations in their firms. From the data, two initial frameworks emerged for how radical innovations were created by these individuals. Four themes emerged associated with what these innovators bring to the organization as an underpinning for being able to radically innovate. Additional themes emerged as to the process by which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 20 publications
3
66
0
3
Order By: Relevance
“…Beyond the benefits from a dedicated licensing function, firms have to integrate these activities by developing "meta strategies" to harmonize their product development and licensing (Kotabe et al, 1996). These strategies need to be directed at maximizing the rents from technology with particular attention to complementary assets (Griffin et al, 2009;Teece, 2007). Despite the importance of an integrated strategy, many firms regard licensing as an isolated stand-alone activity (Davis and Harrison, 2001).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Beyond the benefits from a dedicated licensing function, firms have to integrate these activities by developing "meta strategies" to harmonize their product development and licensing (Kotabe et al, 1996). These strategies need to be directed at maximizing the rents from technology with particular attention to complementary assets (Griffin et al, 2009;Teece, 2007). Despite the importance of an integrated strategy, many firms regard licensing as an isolated stand-alone activity (Davis and Harrison, 2001).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Innovation in established companies has specific characteristics, as also discussed by e g Griffin et al (2009). Cases showed that there is often a possibility to finance interesting ideas and develop them to a stage where they can be assessed from a technical and marked perspective, even together with a customer.…”
Section: Discussionmentioning
confidence: 97%
“…From a micro perspective, literatures of innovation, psychology and sociology focus e g individual creativity as a key enabler for innovation. As Griffin et al (2009) also reports, there is a gap in our understanding between individual creativity on a micro level and organizations' ability to create and commercialize innovations on a macro or mezo level. This paper is the result of a multiple-case (Yin, 1994) research study where 18 cases were in-depth studied through interviews and written material.…”
Section: Introductionmentioning
confidence: 99%
“…In order to stay in the game, corporations not only have to constantly revolutionize their management procedures but also embrace "innovation" as the key factor in their strategic planning (Jung, Kim, & Lee, 2014). Products and services must be able to satisfy consumers' specific needs in order to succeed (Griffin, Price, Maloney, Vojak, & Sim, 2009). Corporations need to have a clear understanding of the needs of their target consumers in order to be able to define the direction of new product development and formulate marketing strategies with higher precision.…”
Section: Introduce the Problemmentioning
confidence: 99%